(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In India a systematic public health administration was introduced under the British rule. The British rulers appointed several committees and enacted a number of Acts in order to develop the health system. After independence the era of scientific planning in India started with the establishment of Planning Commission in 2000. Since then, the Government of India has been giving priority to health matters and several steps have been taken through five year plans.